ENERGY EFFICIENCY IN TRADITIONAL TURKISH HOUSING; PLANNING, INTERIOR ORGANIZATION AND DETAILS - Gecimli, Meryem (PEOPLE: International Journal of Social Sciences, 2018)
Energy efficiency is an important component of ecological sustainability. Traditional houses constructed before the widespread use of reinforced concrete structures are compulsorily compatible with the nature. This is caused by lack of energy efficient technological options. The objective of this paper is to emphasize the planning, interior organization and the details of the Traditional Turkish Housing in terms of energy efficiency. All these factors are shaped by common design principles, climatic and topographic characteristics of the region. In this paper planning, the sun, prevailing wind direction and topography with the sofa (a kind of intermediate space between rooms), summer/winter floor and floor-top storey for living; in the interior organization, interior arrangement and positions of sitting unit sedir (a kind of couch) and the fireplace; in the details, bay window, upper window and so on are evaluated in terms of energy efficiency. The methodology of this paper is qualitative and it depends on literature review and examination of the general characteristics of the Traditional Turkish Housing in Turkey. The significance of this paper is adding interior organization and the details to the energy efficiency field, contrary to the previous research that mostly focuses on the planning piece. The findings of this paper which are planning, interior organization and the details of the Traditional Turkish Housing support the ecological sustainability in terms of energy efficiency.